Acute respiratory infection and influenza-like illness viral etiologies in Brazilian adults - Bellei, Nancy; Carraro, Emerson; Perosa, Ana; Watanabe, Aripuana; Arruda, Eurico [UNESP]; Granato, Celso (Wiley-Blackwell, 2008)
Influenza-like illness (ILI) definitions have been used worldwide for influenza surveillance. These different case definitions can vary with regard to sensitivity and predictive values for laboratory confirmed influenza. The literature has indicated the inclusion of other viruses may be the cause of these variable results. The objective of the study was to evaluate ILI national sentinel criteria and viral etiologies in adults diagnosed with acute respiratory infection ARI) and/or ILI from 2001 to 2003 in Sao Paulo, Brazil. Clinical and laboratory evaluations were observed from 420 adults and collected on a daily basis from outpatient care units at University Hospital. The ILI definition included: fever plus at least one respiratory symptom (cough and/or sore throat) and one constitutional symptom (headache, malaise, myalgia, sweat or chills, or fatigue). DFA and RT-PCR for influenza, parainfluenza, respiratory syncytial virus, adenovirus, enterovirus, coronavirus, rhinovirus, and metapneumovirus were performed on nasal washes and 61.8% resulted positive. The respiratory viruses detected most often were influenza and rhinovirus. ILI was reported for 240/420 patients (57.1%), with influenza and rhinovirus etiologies accounting for 30.9% and 19.6%, respectively. Rhinovirus peak activity was concurrent with the influenza season. These findings highlight the implications of other viruses in ILI etiology and suggest that during the influenza season, this clinical overlap must be considered in the diagnosis and clinical management of patients.
Keywords: influenza; rhinovirus; influenza-like illness